Boron–18F containing positron emission tomography radiotracers: advances and opportunities. (8th August 2014) - Burke, Benjamin P.; Clemente, Gonçalo S.; Archibald, Stephen J.
<x xml:space="preserve">Abstract</x> Standard [18F]fluorination methods to form carbon–fluorine bonds can have some limitations such as low yield and the requirement for harsh reaction conditions. Inorganic approaches include the formation of boron–[18F]fluorine bonds and have the potential to give high specific activities at room temperature forming a bond that is stable in vivo. There is considerable potential in future applications, particularly in relation to multimodal imaging and the provision of rapid efficient labelling protocols. Copyright © 2014 John Wiley & Sons, Ltd.